Family Business: An Entrepreneurial Longer-Term Perspective - Ratna L. Nugroho (Binus Business Review, 2016)
This family business case study is concerned with investigating the issue of the complexity of the many views of the family business research, focusing exclusively on the entrepreneurial concept. In taking this concept, three characteristics were identified in this case study, namely: the attitudes, the skills, and the behavior. Along with these findings, it is suggested that the conceptual model, the so-called “the three circles,” where this three circle has an overlap and identify as a longer-term entrepreneurial perspective within the family-owned enterprise.